2017
DOI: 10.2174/1874325001711010163
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Biologic Factors in Shoulder Disorders

Abstract: Background:Shoulder pathology can cause significant pain, discomfort, and loss of function that all interfere with activities of daily living and may lead to poor quality of life. Primary osteoarthritis and rotator cuff diseases with its sequalae are the main culprits. Management of shoulder disorders using biological factors gained an increasing interest over the last years. This interest reveals the need of effective treatments for shoulder degenerative disorders, and highlights the importance of a comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 176 publications
0
5
0
Order By: Relevance
“…The rate of success with conservative treatment for rotator cuff tears varies widely from 15 to 85% [4][5][6][7][8][9][10]. When conservative therapy is ineffective, open or arthroscopic surgery using suture anchors in a variety of configurations is used with the goal of reducing pain and increasing function [11]. Despite traditional management with surgery to repair partial and full-thickness rotator cuff tears, several studies have shown high failure rates of tendon to bone rotator cuff repairs ranging from 30% to 94% [1,2,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of success with conservative treatment for rotator cuff tears varies widely from 15 to 85% [4][5][6][7][8][9][10]. When conservative therapy is ineffective, open or arthroscopic surgery using suture anchors in a variety of configurations is used with the goal of reducing pain and increasing function [11]. Despite traditional management with surgery to repair partial and full-thickness rotator cuff tears, several studies have shown high failure rates of tendon to bone rotator cuff repairs ranging from 30% to 94% [1,2,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…When conservative therapy is ineffective, open or arthroscopic surgery using suture anchors in a variety of configurations is used with the goal of reducing pain and increasing function [11]. Despite traditional management with surgery to repair partial and full-thickness rotator cuff tears, several studies have shown high failure rates of tendon to bone rotator cuff repairs ranging from 30% to 94% [1,2,11,12]. It can be difficult to determine which types and sizes of tears will benefit from surgical management as tear size and morphology have been shown to be poor predictors for pain and functional scores [13].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, decortication is performed with tendon repair to promote marrow stimulation and the release of mesenchymal stem cells (MSCs). 24,27,36,41 The technique of creating a trough of bleeding bone was proposed by McLaughlin 38 in 1944. However, results from the literature have been inconclusive on whether decortication biologically improves bone to tendon healing and whether the biomechanical risks of decortication merit the theoretical biological benefits.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no human randomized controlled trial has definitively proven that decortication improves bone-to-tendon healing or clinical outcome. 24 Given that the literature regarding the benefits of decortication is limited and largely based on animal models and that the authors have demonstrated a significant decrease in anchor strength, the deleterious effects of decortication may outweigh the theoretical positives.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to augment nonoperative treatment with orthoregenerative approaches exist but have not been widely published in relation to GH chondral conditions. 79 When nonoperative management fails, total shoulder arthroplasty (TSA) has proven to be an excellent option for older patients with OA. In younger patients, and/or in patients with early-stage pathology, reparative and restorative surgical techniques, such as microfracture, autologous chondrocyte implantation, and allograft resurfacing options have been described.…”
Section: Articular Cartilage Pathologymentioning
confidence: 99%